Short-term effect of electroacupuncture on rehabilitation after arthroscopic triangular fibrocartilage complex repair: a randomised study - Chiu-Ming Chang; Cheng-En Hsu; Yu-Chen Lee; Chen-Wei Yeh; Yung-Cheng Chiu (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Electroacupuncture (EA) alleviates chronic pain and acute postoperative pain after several surgical procedures. However, whether EA facilitates postoperative functional recovery after arthroscopic surgery has yet to be determined. This study investigated the short-term effect of EA on a rehabilitation course after arthroscopic triangular fibrocartilage complex (TFCC) repair. Methods Forty-two patients undergoing arthroscopic TFCC repair were randomised to an EA group (n = 19) or control group (n = 23). In the EA group, patients received EA treatment and standard active rehabilitation for 4 weeks. In the control group, patients received standard active rehabilitation for 4 weeks. At the end of the treatment and at the follow-up visit 4 weeks after the treatment, Disabilities of the Arm, Shoulder, and Hand (DASH) scores, wrist range of motion (ROM), handgrip strength, and key pinch strength were collected and analysed. Results The EA group improved significantly than the control group in terms of DASH scores, all wrist motion arcs, and key pinch strength (P < 0.05) at the end of the 4-week treatment and the follow-up visit another 4 weeks later. Conclusion Patients treated with 4 weeks of EA after the arthroscopic TFCC repair had better wrist ROM and DASH scores than patients of control group